Endophytic Trichoderma species from rubber trees native to the Brazilian Amazon, including four new species - Nascimento Brito, Vanessa; Lana Alves, Janaina; Sírio Araújo, Kaliane; de Souza Leite, Tiago; Borges de Queiroz, Casley; Liparini Pereira, Olinto; de Queiroz, Marisa Vieira (Frontiers in Microbiology, 2023)
Fungi belonging to the genus Trichoderma have been widely recognized as efficient controllers of plant diseases. Although the majority of isolates currently deployed, thus far, have been isolated from soil, endophytic Trichoderma spp. are considered to be a promising option for application in biocontrol. In this study, 30 endophytic Trichoderma isolates – obtained from the leaves, stems and roots of wild Hevea spp. in the Brazilian Amazon – were analyzed using specific DNA barcodes: sequences of internal transcribed spacers 1 and 2 of rDNA (ITS region), genes encoding translation elongation factor 1-α (TEF1-α), and the second largest subunit of RNA polymerase II (RPB2). The genealogical concordance phylogenetic species recognition (GCPSR) concept was used for species delimitation. Phylogenetic analysis showed the occurrence of Trichoderma species, such as T. erinaceum, T. ovalisporum, T. koningiopsis, T. sparsum, T. lentiforme, T. virens, and T. spirale. Molecular and morphological features resulted in the discovery of four new species: T. acreanum sp. nov., T. ararianum sp. nov., T. heveae sp. nov., and T. brasiliensis sp. nov. The BI and ML analyses shared a similar topology, providing high support to the final trees. The phylograms show three distinct subclades: T. acreanum and T. ararianum being paraphyletic with T. koningiopsis; T. heveae with T. subviride; and, T. brasiliensis with T. brevicompactum. This study adds to our knowledge of the diversity of endophytic Trichoderma species in Neotropical forests and reveals new potential biocontrol agents for the management of plant diseases.